THE IMPACT OF THE PANDEMIC PERIOD ON STUDENTS’ PHYSICAL ENDURANCE: A LONGITUDINAL STUDY ON MOTOR PARAMETERS (University Arena, 2025)
Background. The COVID–19 pandemic had a significant impact on various aspects of daily life, including children’s physical activity levels. The restrictions imposed during this period led to a considerable decrease in movement and physical exercise among students, which may be correlated with stagnation or even regression in motor development and overall physical fitness. Objectives. The aim of this study was to assess the evolution of students’ physical endurance in lower secondary education by analyzing specific motor parameters measured over three consecutive school years: 2019–2020 (pre-pandemic period), 2020–2021 (pandemic period), and 2021–2022 (recovery period). Methodology. A group of 25 students (11 girls and 14 boys) was evaluated using four motor tests: 25-meter sprint, sit-ups, back extensions from a prone position, and standing long jump. Each parameter was recorded at the beginning and end of each school year. The Friedman test and Dunn-Bonferroni posthoc analysis were used to evaluate statistical differences between the three time points.Results. Most motor parameters showed statistically significant decreases in the 2020–2021 school year compared to the pre-pandemic period. In 2021–2022, notable improvements were observed, particularly in sprint performance and long jump. Running speed and explosive strength declined during the pandemic but showed a positive recovery trend in the following year, without fully reaching initial values. Trunk strength followed a more constant trajectory, yet also improved post-pandemic.Conclusions. The results highlight a significant decrease in students' motor capacity during the pandemic. In the future, it is necessary to develop and implement a structured educational program in the coming school years to support students in regaining and improving their physical endurance.
Keywords: motor capacity; physical endurance; students; pandemic; longitudinal study